1993
DOI: 10.3109/07357909309018870
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Incorporation of 1-β-D-Arabinofuranosylcytosine by Pretreatment with Etoposide

Abstract: We examined the effects of timing of administration of etoposide on cytosine arabinoside (ara-C) incorporation into DNA in L1210 ascites tumor. At 1 hr after injection of ara-C, 3-hr and 6-hr pretreatments with 15 mg/kg of etoposide increased ara-C incorporation to more than 200% as compared to that of ara-C given alone. Simultaneous administration of etoposide, however, decreased ara-C incorporation to 33% of that of ara-C alone. These results might explain the previously reported sequence dependency of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Since cytarabine is an analog of deoxycyctidine, etoposide may influence membrane transport and significantly influence the antitumor effect of etoposide and cytarabine when these drugs are administered in combination. In preclinical studies, etoposide has shown synergistic activity with cytarabine in leukemia cell lines, and the effect of the combination was found to be sequence dependent, with the maximum antileukemic effect observed when etoposide was given 6 h prior to cytarabine infusion [12,13,14,15]. …”
mentioning
confidence: 99%
“…Since cytarabine is an analog of deoxycyctidine, etoposide may influence membrane transport and significantly influence the antitumor effect of etoposide and cytarabine when these drugs are administered in combination. In preclinical studies, etoposide has shown synergistic activity with cytarabine in leukemia cell lines, and the effect of the combination was found to be sequence dependent, with the maximum antileukemic effect observed when etoposide was given 6 h prior to cytarabine infusion [12,13,14,15]. …”
mentioning
confidence: 99%
“…As to the effect of this combination, a sequence-dependent antitumor effect was observed, and administration of EP 6 h before ara-C injection generated the best therapeutic results [28]. Ooi et al [29] demonstrated that the amount of ara-C incorporation into DNA of L1210 cells was increased to more than 200% of the control by a 3-and 6-h pre-administration of EP. They surmised that the period of repair of DNA damage by EP might be the critical time in which ara-C incorporation into DNA is increased.…”
Section: Discussionmentioning
confidence: 96%
“…A number of cytotoxic drugs, such as etoposide, cladribrine, araC, fludarabine and clofarabine have been found to stimulate dCK activity in human and murine leukemic cells [80,81]. It is important to notice that this stimulation requires a basal dCK level in the cells, because in NA-resistant and dCKdeficient cells there was no stimulation of the enzyme (unpublished data from Galmarini).…”
Section: Kinase Deficiencymentioning
confidence: 95%